Methodological indications for motor and sport education in primary school - Giovanni Esposito; Felice Di Domenico (Pensa MultiMedia, 2023)
Motor-sports education in the Italian primary school and its didactic and organizational issues have long been a central theme of the political and scientific debate; however, the various actions carried out so far have not been sufficient to recognize properly educational content and methods, often reducing the time of curricular physical education or the design experiences of motor and sports literacy to simple physical-technical exercises. This study, through archival research with a documentary approach, aims to extrapolate from the thematic nuclei of the national indications for the primary school curriculum those methodological elements that can contribute to a better motor education sport in the age group 6-11 years. The proposals identified are aimed at fostering both the development of technical-tactical skills of sports disciplines adapted to age, and the transversal inferences on social skills (key competences).